ヒト肺亜細葉４Dモデルによる肺拡散能シミュレーション - 北岡, 裕子 (Transactions of Japanese Society for Medical and Biological Engineering, 2016)
I have constructed a 4D subacinar model which contains the capillary space in the alveolar wall (Figure). Oxygen transport is computed by the use of computational fluid dynamics in which incompressive Navier-Stokes equation and the diffusion equation are directly coupled. Simulated results indicated that the blood oxygen partial pressure was little influenced by the alveolar wall thickness but highly dependent of the effective blood flow rate. This simulation study will be useful for investigating respiratory pathophysiology and for developing an implantable artificial lung.